2017
DOI: 10.1158/1078-0432.ccr-16-1946-t
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Patient-Derived Xenografts for Lung Cancer Identifies B2M Inactivation Impairing Immunorecognition

Abstract: Purpose: We aimed to maximize the performance of detecting genetic alterations in lung cancer using high-throughput sequencing for patient-derived xenografts (PDXs). Experimental Design: We undertook an integrated RNA and whole-exome sequencing of 14 PDXs. We focused on the genetic and functional analysis of b2-microglobulin (B2M), a component of the HLA class-I complex. Results: We identified alterations in genes involved in various functions, such as B2M involved in immunosurveillance. We extended the mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…1F) has one of the most negative hazard coefficients, likely reflecting its role in MHC class I antigen presentation of neoantigens to CD8 þ T cells and consistent with reports of this process for immune control of tumors (54). Further, a truncation mutant of B2M can confer resistance to PD-1 blockade in melanoma (55), and mutations in B2M have been shown to disrupt immune surveillance in lung cancer (56). The large negative hazard coefficient associated with HAPLN3, encoding a hyaluronan and proteoglycan link protein, suggests that this gene may warrant further investigation in the context of immune recognition and targeting.…”
Section: Cutaneous Melanoma Is Associated With a Strong Immunogenic Rsupporting
confidence: 79%
“…1F) has one of the most negative hazard coefficients, likely reflecting its role in MHC class I antigen presentation of neoantigens to CD8 þ T cells and consistent with reports of this process for immune control of tumors (54). Further, a truncation mutant of B2M can confer resistance to PD-1 blockade in melanoma (55), and mutations in B2M have been shown to disrupt immune surveillance in lung cancer (56). The large negative hazard coefficient associated with HAPLN3, encoding a hyaluronan and proteoglycan link protein, suggests that this gene may warrant further investigation in the context of immune recognition and targeting.…”
Section: Cutaneous Melanoma Is Associated With a Strong Immunogenic Rsupporting
confidence: 79%
“…References concerning the antibodies and scoring systems used, as well as the details and concentrations of the various treatments are presented in Supplementary Table S2. Western blots and immunohistochemistry were performed using previously described protocols (4). We used previously described criteria to determine B2M, HLA-I, and PD-L1 levels by immunohistochemistry (4).…”
Section: Antibodies Western Blots and Immunostainingsmentioning
confidence: 99%
“…These include defects in tumor immunorecognition, such as downregulation of the HLA-I complex due to gene alterations of its components (either B2M or HLA-A) or at molecules involved in its maturation process (e.g., CALR, TAP1/2, and TAPBP; refs. [2][3][4]. An abnormal increase in the expression of negative controllers of the immune response, such as constitutively high levels of programmed death ligand-1 (PD-L1) expression, also contributes to immune tolerance (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A late relapse patient with metastatic melanoma resistant to CTLA-4 inhibition was found to have biallelic loss of b-2-microglobulin [29,110] . Zaretsky et al [29] also identified a patient with homozygous frameshift deletions of b-2-microglobulin that had developed resistance to PD-1 blockade [28][29][30]192] . Five patients treated with immunotherapy were found to have reduced MHC expression and were not recognized by effector T cells due to loss of b-2-microglobulin expression.…”
Section: Mechanisms Of Secondary Resistancementioning
confidence: 99%